KETERKAITAN INSTRUMEN KEBIJAKAN MONETER DENGAN NERACA PEMBAYARAN DI INDONESIA - Indra Maipita (Universitas Negeri Medan, 2014)
This study aims to determine the monetary policy variable linkages with Indonesia's balance of payments. Using svar and IRF analysis found that the level of α = 0.05, variable monetary policy instruments such as open market operation (OPT), the minimum reserve requirement (GWM), and the discount rate (rDisk) has a significant relationship with the variable balance of payments (BOP) . In fact, all the macroeconomic variables also significantly affect the balance of payments variables, except the variable domestic interest rates. This means that there is a close link between monetary policy instruments with the balance of payments in Indonesia in the period of the study.